Pelaksanaan Pelayanan Komplementer pada Masa Nifas di Praktik Mandiri Bidan Kabupaten Pringsewu - Putri, Nopi Anggista; Komalasari, Komalasari; Fauziah, Nur Alfi; Fitriana, Fitriana; Isnaini, Maulia; Sulistiawati, Yuni (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
The postpartum period is a transitional period where many changes occur, both physically and mentally, which are different for each woman. Efforts to deal with complaints such as perineal injuries, breast problems and even postpatum depression at this time by utilizing complementary therapies using the use of herbs, massage and aromatherapy. Midwives provide complementary services to address these complaints because women tend to believe more in complementary therapies because they feel more natural and safer. This study used a descriptive type of research conducted at the Pringsewu District Midwife's Independent Practice in December 2020 - January 2021. The sample in this study was probably 21 midwives using accidental sampling technique. Data analysis using univariate analysis. The results of the research obtained from people 36 - 45 years of age were 47.6%, with a third diploma education of 52.4%, 42.9% from 11 - 20 years of age and participation in complementary service training partly said that they had attended training a number of trainings 52.4%. As many as 19 (90.5%) midwives have provided complementary services to patients, namely the types of complementary services provided are massage as much as 15 (71.4%), as well as the implementation of complementary services to assist patients in accelerating milk production during the puerperium as many as 18 (85.7%).Masa nifas merupakan masa transisi dimana banyak terjadi perubahan baik fisik maupun mental  yang berbeda pada setiap wanita. Upaya untuk mengatasi keluhan seperti luka perineum, masalah payudara bahkan depresi postpatum pada saat ini dengan memanfaatkan terapi komplementer yaitu penggunaan herbal, pemijatan dan aromaterapi.Bidan melakukan pelayanan komplementer untuk mengatasi keluhan tersebut dikarenakan para wanita cenderung lebih percaya pada terapi komplementer karena dirasakan lebih alami dan aman. Jenis penelitian deskriptif, dilakukan di Praktik Mandiri Bidan wilayah Kabupaten Pringsewu pada bulan Desember 2020 - Januari 2021.Sampel dalam penelitian ini berjumlah 21 bidan dengan teknik accidental sampling. Analisis data yang digunakan adalah analisis univariat.Hasil penelitian ini didapatkan mayoritas Bidan berusia 36 - 45 tahun sejumlah 47,6%, berpendidikan Diploma tiga sejumlah 52,4%, lamanya praktik 11–20 tahun sejumlah 42,9% dan keikutsertaan dalam pelatihan pelayanan komplementer sebagian bersar mengatakan pernah mengikuti pelatihan sejumlah 52,4%. Sebanyak 19 (90,5%) bidan sudah memberikan pelayanan komplementer kepada pasien, yakni jenis pelayanan komplementer yang diberikan adalah pijat sebanyak  15 (71,4%), serta penerapan pelayanan komplementer untuk membantu pasien dalam memperlancar produksi ASI pada masa nifas sebanyak 18 (85.7%).